Properties of acid catalyst lacquer on oil palm trunk (Elaeiss guineensis) surface / Muhammad Nabil Naufal Mohamed Nasim - Mohamed Nasim, Muhammad Nabil Naufal (2014)
The finishing properties of AC(acid catalyst) lacquer and treated and untreated oil palm trunk surface have been studied. The oil palms have been dried by using ethanol and acid catalyst have been applied on its surface. The result show the increase in adhesion and surface roughness test for treated oil palm but its decreased in pencils hardness compare to untreated oil palm. The same trend happened for single layer to double layers of AC suface coating.